Marketing Expansion Through Partnership Cooperation in Order to Increase Cooperative Business Income at the Unpad Community Service Consumer Cooperative (KKIAM) Unpad - Rukanda Ahmad Sulanjana, Iwan Mulyana (PT Wahana Global Education, 2025)
The Insan Abdi Masyarakat Consumer Cooperative (KKIAM) has been operating since 2017 and is now in its eighth year. Various unforeseen events and the pandemic have prevented many plans from being realized. The business managed by the cooperative has not yet generated the revenue expected and has even experienced a decline in turnover, resulting in significant losses over the past two years. Based on preliminary field surveys, the KKIAM Cooperative faces several challenges, including the need to increase sales volume at Samara Dwipa Restaurant, its lack of public awareness, the limited business partnerships needed to increase sales, and the need for product and service development to address business competition. The solution offered to overcome the problems mentioned above, the service team provides direction on sales strategies to increase the sales turnover of Samara Dwipa Restaurant in order to obtain Cooperative income (SHU) to increase even more than in previous years, namely through increasing the network of business partnerships with agencies or other institutions that require cooperative services in the form of providing facilities and infrastructure for meeting/workshop/seminar activities as well as providing catering or providing special catering services for the consumption needs of employees/staff of other agencies/institutions.